2018
DOI: 10.1038/s41598-018-31388-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of sucrose to diminish pore formation in freeze-dried heart valves

Abstract: Freeze-dried storage of decellularized heart valves provides easy storage and transport for clinical use. Freeze-drying without protectants, however, results in a disrupted histoarchitecture after rehydration. In this study, heart valves were incubated in solutions of various sucrose concentrations and subsequently freeze-dried. Porosity of rehydrated valves was determined from histological images. In the absence of sucrose, freeze-dried valves were shown to have pores after rehydration in the cusp, artery and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The important tissue shrinkage observed in the heart due to paraffin embedding (during which the biological samples are totally dehydrated to progressively replace the water content with liquid paraffin) could be avoided by using, for instance, cryostat sections, which do not involve paraffin embedding. However, this usually requires fine-tuning in order to avoid freezing damage (e.g., when and how to use cryoprotectant and an embedding matrix such as OCT and the selection of the freezing method) and results in poor structural preservation, such as ruptures and cracks [37][38][39][40]. These results are added to the well-known limitations of classical 2D histology, namely, the irreversible cut performed in the sample along with a single cutting orientation and an anisotropic voxel size (in the rare case that serial sections were successfully obtained).…”
Section: Discussionmentioning
confidence: 99%
“…The important tissue shrinkage observed in the heart due to paraffin embedding (during which the biological samples are totally dehydrated to progressively replace the water content with liquid paraffin) could be avoided by using, for instance, cryostat sections, which do not involve paraffin embedding. However, this usually requires fine-tuning in order to avoid freezing damage (e.g., when and how to use cryoprotectant and an embedding matrix such as OCT and the selection of the freezing method) and results in poor structural preservation, such as ruptures and cracks [37][38][39][40]. These results are added to the well-known limitations of classical 2D histology, namely, the irreversible cut performed in the sample along with a single cutting orientation and an anisotropic voxel size (in the rare case that serial sections were successfully obtained).…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were reported elsewhere [36] and it was concluded that cross-links that were introduced inter-fibrillarly lead to a decrease in the collagen fiber's ability to shear with each other. To explain this mechanical behavior, a decrease in the collagen's fibril orientation index was suggested elsewhere [28,37]. It was concluded that this could lead to the generation of a more isotropic network in chemically cross-linked pericardial tissue.…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that this could lead to the generation of a more isotropic network in chemically cross-linked pericardial tissue. It was also observed that crosslinking leads to an increase in fiber crimping [28]. It was suggested that the increase in crimping is due to "[.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested, that fresh wet storage of AVA may accelerate calcification [52]. Decellularized heart valves, frozen without protection, presented porosity of histoarchitecture, altering biomechanics; sucrose reduced or diminished its formation [53].…”
Section: Structural Aspects Of the Stored Avamentioning
confidence: 99%